Zastosowanie modelu regresyjnego ze zmiennymi parametrami w rachunku CVP w przedsiębiorstwie - Witkowska, Aleksandra; Witkowski, Marek (The Use of Regressive Model with Variable Parameters in CVP Calculus in an Enterprise, 2007)
The CVP calculus is one of the mainly used instruments in the process of short-term decision making in an enterprise. It allows to include such important economic categories as costs, the extents of activity or profit. A classic CVP calculus is of a static character, because it is built on the data from one period. Furthermore, in the mentioned calculus, the basic problem is the specification of the fixed and variable costs. In the classic meaning, the CVP calculus is made by using the expert method. The above facts make the CVP calculus in its traditional version very coincidential. Because of this, in the thesis we advise to use the regressive model with variable parameters in CVP calculus. Its usefulness was verified on the authentic reference book from the purposely chosen enterprise. The results of the research let us state that the proposed method has both content-related and practical values, because:- it allows to immerse into the "history" of running of the enterprise,- it makes possible to specificate both fixed and variable costs, where the fixed costs are considered as period costs,- it takes CVP calculus holistically,- the calculated measures from CVP's analysis viewpoint have clear interpretation,- it can be useful to make a short-term prognosis parameters in the CVP calculus.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 314-324